OsWRKY26 negatively regulates bacterial blight resistance by suppressing OsXa39 expression - Tun, Win; Vo, Kieu Thi Xuan; Derakhshani, Behnam; Yoon, Jinmi; Cho, Lae-Hyeon; Win, Kay Tha Ye Soe; Lee, Sang-Won; Jung, Ki-Hong; Jeon, Jong-Seong; An, Gynheung (Frontiers in Plant Science, 2025)
Plants are susceptible to infection by various pathogens with high epidemic potential. Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial blight in rice, one of the most significant diseases in both temperate and tropical regions. In this study, we report the identification and characterization of OsWRKY26, a sucrose-inducible transcription factor, that plays a role in the plant defense responses following Xoo infection. We found that mutant plants with defective OsWRKY26 showed enhanced defense response specifically to Xoo, indicating that this transcription factor acts as a negative defense regulator. In contrast, mutant plants did not exhibit higher resistance compared to wild-type (WT) plants when infected with the rice blast fungal pathogen Magnaporthe oryzae. Transcriptomic analysis of mutant and WT plants revealed that several pathogen resistance genes were upregulated in mutants. Of these, we selected OsXa39 for further analysis. Transient expression experiments in rice protoplasts showed that OsWRKY26 repressed the expression of a Luciferase reporter gene driven by the OsXa39 promoter. Chromatin immunoprecipitation analysis revealed that OsWRKY26 binds directly to the promoter region of OsXa39. These findings suggest that OsWRKY26 negatively regulates the defense response during Xoo infection by repressing OsXa39 as well as other pathogen-related genes such as OsXa47, OsBBR1, OsRSR1, OsPR1a, OsPR1-11, OsPR2, and OsPR4c.